Green hydrogen powering sustainable festivals: Public perceptions of generators, production and ownership. (15th March 2023) - Smith, Connor; Bucke, Charlotte; van der Horst, Dan
Abstract: This paper is the first to explore public perceptions about a particular market niche for hydrogen; mobile generators. By utilising a combined research approach including in-situ surveys and online focus groups, this paper explores what festival audience members and residents who live near festival sites think about the displacement of incumbent diesel generator technology with hydrogen alternatives. We investigate if hydrogen production methods are important in informing perceptions and subsequent support, including the extent to which participants are influenced by the organisation or entity that produces the fuel and stands to profit from its sale. In addition to a primary focus on hydrogen energy, we reflect upon how sustainability might be better conceptualised in a festival context. Our findings reveal broad support for hydrogen generators, the use of green hydrogen as a fuel to generate electricity and community-led hydrogen production. Highlights: Outdoor festivals; a high-profile market for early adoption of hydrogen generators. Hydrogen production methods influence perceptions (green hydrogen preferred). Support for community-led hydrogen production. Perceptions and attitudes are not formed in a vacuum, context of learning is vital.